SOME PROPERTIES OF FUZZY MULTIGROUPS - Ifetoye, O. O.; Isah, A. I.; Tella, Y. (FUDMA JOURNAL OF SCIENCES, 2022)
The concept of fuzzy multigroup is an algebraic structure of a fuzzy multiset that generalizes both the classical group and fuzzy group.  In fact, fuzzy multigroup constitutes an application of fuzzy multiset to the elementary theory of classical group.  In this paper, some notions of fuzzy multigroup such as normal series and its properties, fuzzy multigroupoid, fuzzy multimonoid, centralizer of fuzzy multigroup etc., were presented. Some theorems on these together with their proofs were formulated. Some related results on fuzzy multigroups were established